Osmolar gap in hyponatraemia—an exploratory study - Memon, Shoukat; Saeed, Faiza; Alam, Ashar; Chughtai, Javeria; Imtiaz, Salman (Journal of the Pakistan Medical Association, 2024)
Hyponatraemia has indeed been extensively studied from multiple angles, including volume status, tonicity, and aetiology; however, the specific consideration of the osmolar gap (OG) within the context of hyponatraemia and its potential impact on their overall outcomes received limited attention in research. The current study represents an effort to address this gap in our understanding. This prospective exploratory study was conducted on adults aged 14 years and older at the Indus Hospital, Karachi, from 2017 to 2020. The study involved categorising severity of hyponatraemia and volume status. The osmolar gap (OG) was calculated and categorised as either increased (OG>10) or normal (OG<10). Among the 262 patients included in the study, there were 139 females and 123 males. Elevated OG was observed in 141(53.8%) patients. There were 28 (10.7%) recorded fatalities and majority of these individuals had an elevated OG. ---Continue